Reflection of methamphetamine use to research in Türkiye: 2009-2023 - Akkaya, Nurhalime; Aktürk, İlker; Yaman , Ömer Miraç (Journal of Dependence, 2024)
Objective: The increasing use of methamphetamine both globally and in our country has prompted research interest, although the extent of its usage is not as widespread. The limited number of studies on the use of the substance makes it difficult to evaluate individuals who use methamphetamine in terms of quantity and quality. This study aims to examine statistical data regarding the use of methamphetamine in studies conducted in our country and to evaluate these statistics.Method: This research was conducted by bringing together the methamphetamine-related findings of academic studies with statistics on methamphetamine use through a systematic review method. Using key concepts, an in-depth analysis was carried out from 2009, the date when the substance was first encountered in our country, according to TUBİM data, until today.Results: During the research process, data on methamphetamine use was obtained in 140 studies and these data were analyzed in terms of quantity and quality. The data on methamphetamine use has been mostly accessed through master's theses. Generally, there is a limited number of samples involving methamphetamine use in studies. This situation makes it difficult to make inferences about individuals who use methamphetamine.Conclusion: Statistical data on the use of methamphetamine is mostly found in studies on substance use disorders. The number of studies directly related to the use of methamphetamine is limited. Such a comprehensive study compiling data on the use of methamphetamine can provide an insight into the use of methamphetamine in Türkiye.
Keywords: Substance abuse; substance use; amphetamine; stimulant substance